Is it worth placing ventricular pacing wires in all patients post-coronary artery bypass grafting? - Khorsandi, Maziar; Muhammad, Ishaq; Shaikhrezai, Kasra; Pessotto, Renzo (Interactive cardiovascular and thoracic surgery, 2012)
A best evidence topic in cardiac surgery was written according to a structured protocol. The question addressed was whether ventricular pacing wires should be placed routinely in all patients undergoing coronary artery bypass grafting (CABG) regardless of immediate post-cardiopulmonary bypass (CPB) rhythm status. Using the reported search, 142 papers were found, from which 10 papers represented the best evidence on the subject. The author, date and country of 10 publications, study type, patient group studied, relevant outcomes and results are tabulated. Complete atrio-ventricular (AV) block is the main reason for inserting ventricular pacing wires upon conclusion of CABG. Eight studies found complete AV block to be a rare entity post-CABG. The rate of complete AV block in CABG in our review ranged from 0.3 to 24%. The calculated average rate of AV block in all studies was 2.4%. The number needed to treat with ventricular wires to support a patient who develops AV block is 42. One randomized controlled trial found 3% risk of complete AV block post-CABG. Another cohort of 222 patients revealed a rate of 1.8% for complete AV block. For one cohort of 770 patients, post-CABG the rate of complete AV block was found to be 0.3%. In one cohort of 25 patients, there was a rate of 4% for complete AV block post-CABG. Another study of 564 patients revealed a rate of 0.7% for complete AV block. A study of 4999 patients post-CABG reported a rate of 1.2% for complete AV block. In one cohort of 93 patients, there was a 4% risk of complete AV block. Another cohort of 62 patients showed a rate of 1.6% for complete AV block. Only two papers found the rate of complete AV block post-CABG to be as high as 24 and 16%. Both studies were limited by sample size. In conclusion, routine ventricular pacing wire insertion post-CABG is unnecessary given that routine use of ventricular wires can occasionally cause complications such as bleeding and cardiac tamponade and thus is not risk free. We also found that the incidence of complete AV block is probably higher in on-CPB CABG than off-CPB CABG and that AV pacing may be haemodynamically beneficial for some patients postoperatively.